1987
DOI: 10.1113/jphysiol.1987.sp016550
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of cat cutaneous nociceptive C fibres causing tonic and synchronous activity in climbing fibres.

Abstract: SUMMARY1. The input from cutaneous nociceptors to climbing fibres projecting to the forelimb area of the C3 zone in the cerebellar anterior lobe was examined in barbiturate-anaesthetized cats. Climbing fibre responses were simultaneously recorded in single Purkinje cells and as field potentials from the cerebellar surface close to these cells.2. The cutaneous receptive field of the climbing fibres studied were located on the ipsilateral forelimb. All climbing fibres were activated by both non-noxious tactile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…Noxious pinch can cause climbing fiber firing at up to 11 Hz for the duration of the stimulus, lasting several seconds (12). In fact, these experiments were performed in pentobartitone-anesthetized cats and are therefore likely to underestimate the rate of pinch-evoked climbing fiber firing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noxious pinch can cause climbing fiber firing at up to 11 Hz for the duration of the stimulus, lasting several seconds (12). In fact, these experiments were performed in pentobartitone-anesthetized cats and are therefore likely to underestimate the rate of pinch-evoked climbing fiber firing.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that DISC will be induced in vivo by climbing fiber excitation, which produces a significant dendritic Ca 2ϩ influx. Noxious pinch has been shown to induce sustained climbing fiber bursting at 11 Hz in anesthetized cats (12). It is likely that in unanesthetized animals, higher peak climbing fiber frequencies could be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The findings that the A,B-and C-fibre-evoked responses were mediated by the same climbing fibres and that the distribution of the A,f-and C-fibre-evoked climbing fibre field potentials was similar indicate that the C-fibre input to climbing fibres projecting to the C 3 zone is somatotopically organized. In a subsequent paper (Ekerot, Oscarsson & Schouenborg, 1987) it will be shown that the receptive field for climbing fibres is the same for tactile and for noxious stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…This would appear to be sufficient for preventing the occurrence of any conditioning effects. However, olivary discharges have been observed at intervals down to about 40 ms in awake walking cats (Armstrong & Rawson, 1979;Armstrong, Campbell, Edgley, Schild & Trott, 1982), and Ekerot et al (1985) observed that continuous nociceptive stimulation in anaesthetized cats was accompanied by olivary discharge at frequencies exceeding 10 Hz. Eccles et al (1967) discussed the interaction between parallel fibre and climbing fibre input in terms of a 'read-out' hypothesis, where the number of spikes in the c.f.r.…”
Section: Functional Conwiderationsmentioning
confidence: 99%